Modeling sea surface temperatures of the North Atlantic Ocean - Nittaya McNeil (2018)
An assessment of the trends and patterns of sea surface temperatures in the North Atlantic Ocean was carried out using statistical methods. The data were obtained from the climate research unit, comprising twenty-five 5 by 10° regions, covering latitudes 40 to 65°N and longitudes 10 to 60°W between 1973 and 2008. Linear regression was initially used to model the seasonally adjusted sea surface temperatures. The data was filtered with a second order autoregressive process to remove autocorrelations between temperature lags. A multivariate linear regression model was then fit to the data to account for the spatial correlation, giving the covariance matrix of the estimated slopes. A three-factor model was fit to the covariance matrix to form three larger regions. A spline linear regression model with one knot at 1990 was then fit to these three regions. The temperatures in these three regions were found to increase by approximately 0.13 °C per decade during 1973-1989. During 1990-2008, the increase in temperatures in the two of three larger regions identified by the factors analysis was at least 0.40 °C per decade. © 2013 Springer-Verlag Wien.